Generalized fractals in semimetric spaces. (July 2022) - Bessenyei, Mihály; Pénzes, Evelin
Abstract: The aim of the present paper is to extend the classical fractal theory using condensing maps and generalized contractions of semimetric spaces. Our method is independent from the approach of Hutchinson: It is based on the Kuratowski measure of noncompactness and avoids completely the Blaschke Completeness Theorem.